Pengaruh Variabel BOPO, NOM Dan CAR Terhadap Profitabilitas Bank Umum Syari’ah di Indonesia pada Masa Pandemi Covid-19 - Rifa'atul Munawaroh; Bambang Dwi Suseno; Sulaeman Jajuli (TSARWAH, 2022)
Covid-19 has various impacts is the economic sector, especially the banking sector. Banks are constrained to get the level of profit. Profitability can be reflected in how effective the bank's management is in managing the funds entrusted to it to generate profits. The objectives of this study to determine the effect of BOPO, NOM, and CAR on the profitability of Islamic Commercial Banks during the Covid-19 pandemic. The population in this study were all Islamic Commercial Banks in Indonesia with a total of 13 banks. Use secondary data, namely financial reports that had been published. The amount of data analyzed is 26 months. Technical data analysis used Partial Least Squares (PLS). The results showed that; 1) The coefficient value of the effect of BOPO on Profitability was 0.956, which means there was a positive influence and the T-Statistics value was 3.166. 2) The coefficient value of the effect of BOPO on CAR was 0.511, which means there was a positive influence and the T-Statistics value was 6.666. 3) The coefficient value of the effect of BOPO on NOM is 0.652 which means there is a positive influence and the value of T-Statistics is 12,414. 4) The coefficient value of the influence of NOM on Profitability is 0.652 which means there is a positive influence and the value of T-Statistics is 8.698. 5) The coefficient value of the effect of CAR on Profitability is 0.956, which means there is a positive influence and the T-Statistics value is 2.387.